Histological Chorioamnionitis and Funisitis as New Risk Factors for Retinopathy of Prematurity: A Meta-analysis - El Emrani, Salma; Jansen, Esther J.S.; Goeman, Jelle J.; Lopriore, Enrico; Termote, Jacqueline U.M.; Schalij-Delfos, Nicoline E.; van der Meeren, Lotte E. (American Journal of Perinatology, 2023)
Objective The role of placental inflammation in neonatal morbidities is underestimated due to lack of placental examination. This meta-analysis aims to assess the association between histological chorioamnionitis (HCA) with and without funisitis (FUN) and risk of retinopathy of prematurity (ROP).Study Design Forty-five studies reporting (unadjusted) data on HCA without FUN and HCA with FUN in neonates with ROP were included. Primary outcomes were any stage ROP and severe ROP. Potential confounders explored were gestational age (GA) at birth, birthweight, maternal steroid use, necrotizing enterocolitis, sepsis (suspected/proven) and mechanical ventilation duration.Results Neonates with HCA had increased risk for any stage ROP (odds ratio [OR] 1.8; 95% confidence interval [CI] 1.3–2.4) and severe ROP (OR 1.5; 95% CI 1.2–1.8) compared with neonates without HCA. The rates of any stage ROP (OR 1.8; 95% CI 1.4–2.2) and severe ROP (OR 1.4; 95% CI 1.1–1.6) were higher in neonates with FUN compared with neonates without FUN. Multivariate meta-regression analysis suggests that lower GA increases the effect size between FUN and severe ROP.Conclusion This meta-analysis confirms that presence of HCA and FUN are risk factors for any stage ROP and severe ROP. Structured histological placental examination of HCA and FUN may be a tool to further refine the ROP risk profile.Key Points
Keywords: retinopathy of prematurity; histological chorioamnionitis; funisitis; prematurity; meta-analysis